PKM Optimalisasi Sumber Belajar Rumah Smart Farming Sebagai Sarana Belajar Dan Peningkatan Literasi Pangan Untuk Mendukung MBG Di Sekolah Alam Kubang Raya - Hudi, Ilham (LPPM UMRI, 2025)
Abstract Sekolah Alam Kubang Raya, located on Jl. Pesantren, Siak Hulu District, Pekanbaru City, is situated within the same area as Universitas Muhammadiyah Riau, approximately 10.7 km away. The smart farming learning house program serves as an innovative learning resource that can be utilized as a medium for students to enhance food literacy. Developing food literacy from an early age is crucial for students to understand various aspects of food security, environmental sustainability, and the application of technology in agriculture. The community service method applied in this program is designed to optimize the implementation of a smart farming house based on the Internet of Things (IoT) technology. This program is dedicated to providing educational guidance in improving students’ knowledge about healthy food, modern farming techniques, and raising awareness of technology utilization to support food sustainability. The implementation of this activity is expected to increase school members’ awareness of managing food resources with appropriate technology, thus fostering students’ comprehensive food literacy. Therefore, training on smart farming practices and IoT technology is essential to equip students with the necessary skills to face future challenges in food security.